2009
DOI: 10.1080/09593330902911689
|View full text |Cite
|
Sign up to set email alerts
|

Performance of sequencing batch biofilm and sequencing batch reactors in simultaneousp‐nitrophenol and nitrogen removal

Abstract: The objective of this study is to evaluate the performance of sequencing batch biofilm reactors (SBBRs) and sequencing batch reactor (SBR) in the simultaneous removal of p-nitrophenol (PNP) and ammoniacal nitrogen. SBBRs involved the use of polyurethane sponge cubes and polyethylene rings, respectively, as carrier materials. The results demonstrate that complete removal of PNP was achievable for the SBR and SBBRs up to the PNP concentration of 350 mg/l (loading rate of 0.368 kg/m3 d). At this loading rate, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…A group of researchers [10] investigated the performance of MBSBR and SBR in simultaneous p-nitrophenol and nitrogen removal. Their results demonstrate that complete removal of PNP was achievable for the SBR and MBSBR up to loading rate of 0.368 kg/m 3 per day.…”
Section: Introductionmentioning
confidence: 99%
“…A group of researchers [10] investigated the performance of MBSBR and SBR in simultaneous p-nitrophenol and nitrogen removal. Their results demonstrate that complete removal of PNP was achievable for the SBR and MBSBR up to loading rate of 0.368 kg/m 3 per day.…”
Section: Introductionmentioning
confidence: 99%
“…This assures biofilms attachment on MRH and allows MRH to function like a carrier material in a sequencing batch biofilm reactor (SBBR). The better performance of SBBR is due to the bioactivity of attached-growth biomass being less inhibited by toxic constituents than the suspended-growth biomass [25]. In this study, the presence of attached biofilm on the surface of the MRH could not be confirmed experimentally due to interference caused by the overwhelming presence of the suspended biomass.…”
Section: Role Of Adsorbents In Leachate Treatment Under Sbr Operationmentioning
confidence: 95%
“…Goh et al [32] reported that a sequencing batch biofilm reactor (SBBR) (with polyurethane sponge cubes) showed better performance than a SBR, as the SBBR achieved almost complete removal of ammonia-nitrogen, while the SBR achieved on average 86% when both were used in the simultaneous removal of p-nitrophenol and ammonianitrogen. Kim et al [33] achieved 87% NH + 4 -N removal efficiency at a loading of 0.17 g/l.day in an aerobic reactor in an anoxic-aerobic suspended growth system, which was comparable with the present findings.…”
Section: Aerobic Reactor (B3)mentioning
confidence: 98%